Uptake of Human Papilloma Virus vaccine among young women living in fishing communities in Wakiso and Mukono districts, Uganda. - Muteebwa Laban; Gertrude Nanyonjo; Mathias Wambuzi; Ali Ssetaala; Geofrey Basalirwa; Dan Muramuzi; Jacqueline Kyosiimire Lugemwa; Brenda Okech; Ali Mirzazadeh (Public Library of Science (PLoS), 2024)
Human Papilloma Virus (HPV) is a preventable cause of cervical cancer, the commonest cancer among women in Uganda. The Uganda Ministry of Health included the HPV vaccine in the free routine immunization schedule since 2015. Five years after this policy, we assessed the uptake of the HPV vaccine and associated socio-demographic factors among young women living in fishing communities in Central Uganda in 2020. We analyzed secondary data from 94 young women aged 9-25 years who were recruited from the two fishing communities (Kasenyi landing site and Koome Island) in a primary study that aimed to promote awareness of maternal and childhood vaccines. We assessed uptake of the HPV vaccine as the proportion of participants who self-reported to have ever received at least one dose of the HPV vaccine. We assessed the socio-demographic factors associated with HPV vaccine uptake using a modified Poisson regression model adjusted for clustering by study site in STATA version 17. The mean (standard deviation) age of study participants was 21.1 (3.1) years and most (81.9%) of them were from Kasenyi landing site. The uptake of the HPV vaccine was 10.6% [95% Confidence Interval (CI) 5.6, 18.9]. After adjusting for covariates, being 13-19 years old (adjusted prevalence ratio [aPR] 5.52, 95%CI 1.69, 18.00) and of Catholic religion (aPR 5.55, 95%CI 1.53, 20.16) were significantly associated with HPV vaccine uptake. The HPV vaccine uptake was very low, despite the reported 99% national coverage of HPV vaccination program for the first dose at the end of 2019. Age and religion showed to be important determinants of the HPV vaccine uptake. Reasons for such very low uptake of HPV vaccinations need to be carefully assessed to find effective strategies to improve it.